In vitro and In silico Analysis of Pomegranate (Punica granatum L.) Fruit Powder as Pancreatic Lipase and α-Amylase Inhibitor. (October 2020) - Dewi, Andi Alfira Ratna F; Muntholib,; Subandi,
Abstract: This study aims are to produce pomegranate powder, then to extracted with boiling water and to find out the phytochemical compounds, total phenolic compounds (TPC), total flavonoid compounds (TFC) and its inhibitory activity against pancreatic lipase by in vitro analysed. Besides of that, a compound that exist in pomegranate will also be in silico analysed by docking technique, for its binding with the α-amylase enzyme compared to acarbose. In vitro inhibition tests were conducted by titrimetric method, using olive oil as substrate, pancreatic lipase as enzymes, and orlistat as a standard inhibitor; meanwhile the in silico test was conducted by molecular docking techniques using human α -amylase as a receptor and acarbose and a compound in pomegranate (quercetin) as ligand. The result has shown that hot water extracts of pomegranate fruits powder (1.5 gr/150 ml) contained flavonoids, polyphenols, and alkaloids and TPC and TFC contents were 2.090 ppm and 2.058 ppm, respectively; had pancreatic lipase inhibition activity of 0.54 times compared to orlistat at the same mass (120 mg), and based on its molecular docking, quercetin, a compound in the pomegranate can bind to the α-amylase enzyme in a position that is relatively the same as acarbose, even with slightly larger affinity bindings.